High Order Finite Difference WENO Methods with Unequal-Sized Sub-Stencils for the Degasperis-Procesi Type Equations (Communications in Computational Physics, 2022)
In this paper, we develop two finite difference weighted essentiallynon-oscillatory (WENO) schemes with unequal-sized sub-stencils for solving theDegasperis-Procesi (DP) and $μ$-Degasperis-Procesi ($μ$DP) equations, which containnonlinear high order derivatives, and possibly peakon solutions or shock waves. Byintroducing auxiliary variable(s), we rewrite the DP equation as a hyperbolic-ellipticsystem, and the $μ$DP equation as a first order system. Then we choose a linear finitedifference scheme with suitable order of accuracy for the auxiliary variable(s), andtwo finite difference WENO schemes with unequal-sized sub-stencils for the primalvariable. One WENO scheme uses one large stencil and several smaller stencils, andthe other WENO scheme is based on the multi-resolution framework which uses a series of unequal-sized hierarchical central stencils. Comparing with the classical WENOscheme which uses several small stencils of the same size to make up a big stencil, bothWENO schemes with unequal-sized sub-stencils are simple in the choice of the stenciland enjoy the freedom of arbitrary positive linear weights. Another advantage is thatthe final reconstructed polynomial on the target cell is a polynomial of the same degree as the polynomial over the big stencil, while the classical finite difference WENOreconstruction can only be obtained for specific points inside the target interval. Numerical tests are provided to demonstrate the high order accuracy and non-oscillatoryproperties of the proposed schemes.
Keywords: High order accuracy; weighted essentially non-oscillatory schemes; Degasperis-Procesi equation; $μ$-Degasperis-Procesi equation; finite difference method; multi-resolution.